2020
DOI: 10.3390/cancers12061528
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Type Distribution of High-Risk Human Papillomavirus (HPV) in Breast Cancer: A Qatar Based Study

Abstract: Human papillomavirus (HPV) has been implicated in the etiology of a variety of human cancers. Studies investigating the presence of high-risk (HR) HPV in breast tissue have generated considerable controversy over its role as a potential risk factor for breast cancer (BC). This is the first investigation reporting the prevalence and type distribution of high-risk HPV infection in breast tissue in the population of Qatar. A prospective comparison blind research study herein reconnoitered the presence of twelve H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
(35 reference statements)
4
18
0
Order By: Relevance
“…In the State of Qatar, Sher et al, 2020 [216] examined a cohort of 150 freshly obtained breast tissue specimens (50 benign breast lesions, 50 breast cancer, and 50 normal breast tissues) and reported the presence of high-risk HPV in 10% of the subjects with breast cancer, of which 12.12% were invasive carcinomas [216]. Concomitantly, our group examined 74 cases of breast cancer from 2008 to 2019 that were treated surgically in Hamad General Hospital, Qatar, and detected high-risk HPVs in 65% of the cases with a significant correlation between HPV+ breast cancer and triple-negative breast cancer subtype [217].…”
Section: In Gcc Countries and Yemenmentioning
confidence: 99%
“…In the State of Qatar, Sher et al, 2020 [216] examined a cohort of 150 freshly obtained breast tissue specimens (50 benign breast lesions, 50 breast cancer, and 50 normal breast tissues) and reported the presence of high-risk HPV in 10% of the subjects with breast cancer, of which 12.12% were invasive carcinomas [216]. Concomitantly, our group examined 74 cases of breast cancer from 2008 to 2019 that were treated surgically in Hamad General Hospital, Qatar, and detected high-risk HPVs in 65% of the cases with a significant correlation between HPV+ breast cancer and triple-negative breast cancer subtype [217].…”
Section: In Gcc Countries and Yemenmentioning
confidence: 99%
“…Various recent studies have revealed the composition of the microbiome in breast cancer tissue. Specifically, the human papillomavirus (HPV) is one of the most common microorganisms present in breast cancers when compared to other normal breast controls [ 60 , 62 , 63 ]. Interestingly, several studies suggest that the HPV might be a critical trigger for breast ductal carcinomas due to its capacity to immortalize resident epithelial cells [ 64 - 66 ].…”
Section: Microbiome: General Facts and Its Role In Cancermentioning
confidence: 99%
“…Breast cancer (BC) microbiome ( Figure 1 ) is hypothesized to be affected by bacteria-related inflammation in the mammary ducts and glands disrupting the hierarchy of stem cells. Several recent studies focus on the intra-tissue microbial and the viral composition in BC [e.g., human papillomavirus (HPV); Nejman et al, 2020 ; Sher et al, 2020 ]. HPVs are more abundant in BCs compared to benign breast and normal breast controls ( Lawson et al, 2016 ).…”
Section: Breast Intracellular Microbiomementioning
confidence: 99%
“…The effect of HPV on BC has been investigated for years ( Di Lonardo et al, 1992 ; Widschwendter et al, 2004 ; Sher et al, 2020 ). The presence of HPV in BC tissue has resulted in increased histopathological activity in the tumor ( Al-Badry et al, 2019 ).…”
Section: Breast Intracellular Microbiomementioning
confidence: 99%
See 1 more Smart Citation